LEUKOSITOSIS BER-FLAGGING BINTANG () BERPOTENSI ADANYA INTERFERENSI ALAT ANALISIS HEMATOLOGI OTOMATIS - Christine Sugiarto; Leni Lismayanti; Nadjwa Zamalek Dalimoenthe (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Leukocytosis is a condition in which there is an increasing number of white blood cell count in the peripheral blood compared to thenormal range based on age. Several conditions can amplify leukocyte count from haematological auto analyzers, not only those whichcorrespond to the pathologic and physiologic condition, but also with other factors, such as diluent and haematological auto analyzer’smethods. The information about these factors should be evaluated to lessen errors in the patient’s diagnosis and therapy. This casereport describes a leukocytosis in a 35-day old baby boy, diagnosed as duodenal obstruction, admitted in Paediatric Surgery Department,Hasan Sadikin Hospital, Bandung. Discrepancies occurred in this patient’s leukocyte count with some different haematological autoanalyzers. The leukocyte count from the auto analyzer by impedance method and ammonium salt diluent was 129.200/mm3 which wasindicated by a star-flagged (), while from the auto analyzer with light scatter method and anhydrous sodium sulphate and sodiumchloride diluent was 9.200/mm3, from manual count by the counting chamber with Turk diluent was 14.200/mm3 and the estimationby peripheral blood smear was 7.000–10.000/mm3. False leukocytosis by auto analyzer with impedance method was caused by thelimitation of the analyzer’s method and by the erythrocyte lysine reagent (diluent) using ammonium salt. As investigated in this case,the interferences were thought as being caused by the Lyses-resistant Red Blood Cells, thus the non-lysed/lyses cells which were enlargedin size were identified as leukocytes other than erythrocytes. It can be that the white blood concluded cell count examination which isindicated by star-flagged (), or white blood cell count >100.000/mm3 must be confirmed by manual examination (counting chamberand peripheral blood smear) or by another haematological auto analyzer method that has a different and more potent diluent